2019
DOI: 10.1080/09540261.2018.1531831
|View full text |Cite
|
Sign up to set email alerts
|

Same behaviours, different reasons: what do patients with co-occurring anorexia and autism want from treatment?

Abstract: Key words: Qualitative, Autism, anorexia, treatment, comorbidityResearch suggests that up to 1 in 4 individuals with anorexia nervosa (AN) may be on the autistic spectrum, and that these autistic traits may not have been recognised or diagnosed prior to eating disorder (ED) treatment. Significantly, these heightened autistic traits are associated with poorer treatment outcomes, suggesting that treatment may need to be adapted for this population. The purpose of this study was to explore with people with AN on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
99
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(117 citation statements)
references
References 46 publications
12
99
1
2
Order By: Relevance
“…Autism is a neurodevelopmental disorder associated with differences in social communication, and restricted behaviours and interests (1). People with AN exhibit heightened levels of autistic traits compared to HC (28), and qualitative research suggest that altered interoception could contribute to disordered eating in autistic adults (29,30). Research suggests that interoceptive accuracy may be lowered in autism (31,32), although other studies have found no differences in autism compared to HC (33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…Autism is a neurodevelopmental disorder associated with differences in social communication, and restricted behaviours and interests (1). People with AN exhibit heightened levels of autistic traits compared to HC (28), and qualitative research suggest that altered interoception could contribute to disordered eating in autistic adults (29,30). Research suggests that interoceptive accuracy may be lowered in autism (31,32), although other studies have found no differences in autism compared to HC (33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…Sensory differences driven by alterations in bottomup processing are common in autism, to the extent that atypical responses to sensory stimuli have been included as a diagnostic criteria in the most recent edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) [1,11]. Qualitative research on co-occurring autism and AN has highlighted sensory sensitivities as potentially contributing to eating difficulties in AN; however, this area remains under-explored using experimental methods [12,13]. This is significant as sensory sensitivity may play a role in neurobiological models of AN maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst most ED clinicians recognised the importance of considering autism in AN treatment, many did not feel they had enough knowledge to provide adequate treatment for this client group (Kinnaird et al 2017). In line with this finding, autistic women in treatment for AN in the UK reported that they experience unique needs associated with their autism, which they feel are not met by currently offered treatments (Kinnaird et al 2019b). Although there will be some differences in how ED services are organised across different countries, given the lack of knowledge on the overlap between the two conditions and lack of official guidance on how to recognise and support autistic women in ED services, these findings are likely to also apply to the service experience of women in other countries.…”
mentioning
confidence: 99%
“…Despite a significant proportion of autistic women in ED services, current service provision does not acknowledge or address their needs (Kinnaird et al 2017(Kinnaird et al ,2019b. Evidence from both the UK and Sweden suggests that women with high autistic traits benefit less from current interventions and care pathways and have worse outcomes than other women with AN, experiencing especially low recovery rates and levels of functioning (Nielsen et al 2015;Tchanturia et al 2017Tchanturia et al ,2016Nazar et al 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation